2017
DOI: 10.1038/ncomms14169
|View full text |Cite
|
Sign up to set email alerts
|

Edge reactivity and water-assisted dissociation on cobalt oxide nanoislands

Abstract: Transition metal oxides show great promise as Earth-abundant catalysts for the oxygen evolution reaction in electrochemical water splitting. However, progress in the development of highly active oxide nanostructures is hampered by a lack of knowledge of the location and nature of the active sites. Here we show, through atom-resolved scanning tunnelling microscopy, X-ray spectroscopy and computational modelling, how hydroxyls form from water dissociation at under coordinated cobalt edge sites of cobalt oxide na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
148
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(162 citation statements)
references
References 50 publications
13
148
1
Order By: Relevance
“…The second point of view agrees well with our observation of the labyrinth structure (figure 4, c) which appears to be originating from additional dissociative adsorption from the rest gas, as described above. The strong dissociative properties are also in line with our recently described study of the dynamics in water dissociation and hydroxylation on Co-O bilayer edges 12 , however the process on trilayers leading to the initial formation of the √3 × √3 30° superstructure must take place at a much faster rate.…”
Section: Hydroxyl Overlayersupporting
confidence: 65%
See 2 more Smart Citations
“…The second point of view agrees well with our observation of the labyrinth structure (figure 4, c) which appears to be originating from additional dissociative adsorption from the rest gas, as described above. The strong dissociative properties are also in line with our recently described study of the dynamics in water dissociation and hydroxylation on Co-O bilayer edges 12 , however the process on trilayers leading to the initial formation of the √3 × √3 30° superstructure must take place at a much faster rate.…”
Section: Hydroxyl Overlayersupporting
confidence: 65%
“…This overlayer structure (referred to as a "labyrinth" structure) is estimated to reach an OH coverage of up to 0.5 (i.e. now a total stoichiometry of CoOOH 0.5 ), similar to the case of our recent study of water dissociation on Co-O bilayer islands reaching saturation at exactly 50% hydroxylation on the island basal plane 12 , where the islands exhibit similar linear features in STM together with an underlying √3 × √3 30° superstructure. The additional hydroxylation compared to the density of 0.33 in the OH superstructure proposed in figure 4b is likely to arise from further dissociative adsorption of H 2 O or H 2 from the rest gas on the pristine islands, whereas such an additional hydroxylation would not result in a "labyrinth" structure starting from the alternative √3 × √3 30° with an OH density of 0.66.…”
Section: Hydroxyl Overlayermentioning
confidence: 58%
See 1 more Smart Citation
“…[15,16] Both are comprised of layers of edgesharing MO(H) 6 octahedra and show increased OER activity and am ore-positive (nominal) M 2+/3+ reduction potential upon Fe-incorporation. [20,21] Herein we use operando XAS to study Co(Fe)O x H y .W e find clear evidence for Fe oxidation and FeÀOb ond shortening at OER relevant potentials,c onsistent with the hypothesis that high-valent Fe is involved in the OER mechanism. [6] Gong et al found that CoO x with Fe 3+ ions adsorbed from solution was more active than co-deposited Fe 4.4 Co 95.6 O x .…”
mentioning
confidence: 69%
“…This is consistent with conversion from the hydroxide to oxyhydroxide phase during the Co 2+/3+ oxidation wave (Supporting Information, Figure S1C). [17,18,21] Upon Fe addition, Co oxidation during the OER is suppressed, evidenced by the lack of significant change in the Co K-edge energy when stepping the potential to OER conditions ( Figure 2B,C). E O 2 =OH À where the OER occurs.There is no change in the pre-edge feature.This shift is most likely due to afraction of Co being oxidized from Co 3+ to Co 4+ ,c onsistent with reports of Co 4+ during the OER.…”
mentioning
confidence: 99%